2021
DOI: 10.1182/blood-2021-145977
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the International Myeloma Working Group Frailty Score in Capturing Health-Related Quality of Life Profile of Patients with Relapsed Refractory Multiple Myeloma

Abstract: Background Clinical decision-making in patients with relapsed refractory multiple myeloma (RRMM) is challenging and identification of patients who can benefit the most from a given therapy is of critical importance. The International Myeloma Working Group (IMWG) index is one of the most robust scores to evaluate frailty, and it has been validated for patients with newly diagnosed MM. However, little is known on its applicability in the setting of RRMM and of its relationships with patient-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…We then used PRFP to determine the prevalence of frailty in our study sample. Our findings were in line with a previous prospective cohort study of RRMM patients, albeit one in which the International Myeloma Working Group (IMWG) frailty index was used [28]. Similar to our analysis, 53% of patients in their study were fit, 23% were pre-frail, and 24% were frail [28].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We then used PRFP to determine the prevalence of frailty in our study sample. Our findings were in line with a previous prospective cohort study of RRMM patients, albeit one in which the International Myeloma Working Group (IMWG) frailty index was used [28]. Similar to our analysis, 53% of patients in their study were fit, 23% were pre-frail, and 24% were frail [28].…”
Section: Discussionsupporting
confidence: 91%
“…A key benefit to using patient self-report to measure frailty is that it incorporates the patient’s voice and is a more patient-centric approach [ 28 ]. In their recent study, Efficace et al found a strong correlation between RRMM patients’ frailty status, as measured by the IMWG frailty index, and their self-reported physical functioning and symptom burden as captured by the EORTC QLQ-C30 [ 28 ]. The authors noted that fit , pre-frail , and frail patient groups had distinct patient-reported Health-Related Quality of Life (HRQoL) profiles and concluded that their work paves the way for a patient-centered frailty index [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations